Neighborhood Indicators of Employment and Economic Family Well-Being for Zipcode 53233 - (:unkn) unknown (My University, 2004)
This neighborhood indicators report assesses employment, economic and welfare changes in ZIP code 53233 based on eleven years of institutional data. The 2002 income tax data (based on state tax returns filed by April 2003) provides income earnings data that is three years more current than the 1999 incomes reported by the U.S. Census. Funding for the report was provided by the Greater Milwaukee Foundation and the City of Milwaukee Community Development Block Grant Program. Among the areas addressed are: age of the population, family income and workforce growth, earned income tax credits, working families with income below poverty, child care availability and subsidies, families receiving public assistance, business activity in the neighborhood, housing trends, transportation barriers, and neighborhood safety.
Keywords: neighborhood indicators; family income; crime; public assistance; business trends